A rare case of isolated tuberculous epididymitis in a young man - Momin, Majed Basit; Satyanarayana, Sandeep; Aluri, Anamika (IMC Journal of Medical Science, 2019)
Genitourinary tuberculosis is the second most common extrapulmonary tuberculosis (ETB), after lymph nodes. Isolated tuberculous epididymitis (ITE) is a rare entity among genitourinary tuberculosis and is defined as epididymitis without clinical evidence of either renal or prostate involvement. We present a case of epididymal tuberculosis in a 26 year old male which presented as a right scrotal mass. We discussed this case to emphasize that tuberculous etiology should also be considered in the differential diagnosis of scrotal mass besides malignancy, and an image guided fine needle aspiration cytology (FNAC) and stain for acid fast bacilli (AFB) play crucial role in diagnosis and treatment. IMC J Med Sci 2019; 13(1): 003